What is money in a critical macro-finance framework? - Steffen Murau; Tobias Pforr (Finance and Society, 2020)
This forum contribution explains how analyzing the creation, distribution, and destruction of contemporary credit money is placed centre stage in the emerging field of critical macro-finance. This approach not only involves traditional forms of money but also "shadow money": private credit instruments which are not regulated as money from a legal standpoint, but in many respects are functionally equivalent to "established" forms of money. To connect different positions in this discourse, we propose three core criteria for defining shadow money as a baseline position for future critical macro-financial research.
Keywords: 300